Single-Cell Transcriptomics Uncover Key Regulators of Skin Regeneration in Human Long-Term Mechanical Stretch-Mediated Expansion Therapy - Sun, Yidan; Xu, Luwen; Li, Yin; Lin, Jian; Li, Haizhou; Gao, Yashan; Huang, Xiaolu; Zhu, Hainan; Zhang, Yingfan; Wei, Kunchen; Yang, Yali; Wu, Baojin; et al. (Frontiers in Cell and Developmental Biology, 2022)
Tissue expansion is a commonly performed therapy to grow extra skin in vivo for reconstruction. While mechanical stretch-induced epidermal changes have been extensively studied in rodents and cell culture, little is known about the mechanobiology of human epidermis in vivo. Here, we employed single-cell RNA sequencing to interrogate the changes in the human epidermis during long-term tissue expansion therapy in clinical settings. We also verified the main findings at the protein level by immunofluorescence analysis of independent clinical samples. Our data show that the expanding human skin epidermis maintained a cellular composition and lineage trajectory that are similar to its non-expanding neighbor, suggesting the cellular heterogeneity of long-term expanded samples differs from the early response of the expansion. Also, a decrease in proliferative cells due to the decayed regenerative competency was detected. On the other hand, profound transcriptional changes are detected for epidermal stem cells in the expanding skin versus their non-expanding peers. These include significantly enriched signatures of C-FOS, EMT, and mTOR pathways and upregulation of AREG and SERPINB2 genes. Associated ligand-receptor pairs and signaling pathways based on CellChat were revealed. Together, our data present a single-cell atlas of human epidermal changes in long-term tissue expansion therapy, suggesting that transcriptional change in epidermal stem cells is the major mechanism underlying long-term human skin expansion therapy. We also likely represented novel therapeutic targets to promote human skin expansion efficiency in the future.